Assessment of Coverage and Quality of Selected Clinical Chemistry Tests among Medical Laboratories of Health Facilities in Jimma Zone, South West Ethiopia - Aklilu Getachew; Waqtola Cheneke; Yaregal Asres; Shiferaw Bekele; Estifanos Kebede (Journal of Tropical Medicine)
Background. Medical laboratories play essential roles in measurement of analyte in clinical sample for the diagnosis and monitoring of diseases. Thus, data generated from the laboratory have to be reliable for which strict quality assurance is maintained. Objective. To assess the coverage and quality of selected clinical chemistry tests among medical laboratories of health facilities in, Jimma Zone, South West Ethiopia. Methods. A cross-sectional study was conducted at Jimma Zone on health facilities from August 15 to September 15, 2014. Eighty-six health facility laboratories were included in the study. We classified laboratories into laboratories with clinical chemistry service and those without clinical chemistry service clusters and those with clinical chemistry laboratory were again clustered according to their level. Data were collected by direct observation, interview, and proficiency testing (PT). The collected data were analyzed and compared with CLIA PT goal for TEa by considering total allowable error ± 20%, ±10%, ±15%, and ±20 for each analyte, ALT, glucose, creatinine, and total bilirubin, respectively. Result. From total of 86 health facilities with laboratories, 23.3% (n=20) had clinical chemistry service, of which 77.2% results were reported outside of the allowable error limit. Conclusion. According to this study the availability of clinical chemistry test service was very minimal and facilities giving the service do not fulfill the minimum standard for quality; thus clients were either getting wrong clinical decision or misdiagnosed. Therefore, the external and internal quality assessment programs should be reviewed very well. Those laboratories whose report was outside of the allowable error should have to report results with the appropriate reference range so that physicians consider that. Establishment of local clinical chemistry reference range can also minimize the problem.